Cognitive dysfunction in atrial fibrillation. Issue 12 (December 2018) - Madhavan, Malini; Graff-Radford, Jonathan; Piccini, Jonathan; Gersh, Bernard
Abstract Atrial fibrillation (AF) is the most common arrhythmia in adults, and its incidence and prevalence increase with age. The risk of cognitive impairment and dementia also increases with age, and both AF and cognitive impairment or dementia share important risk factors. In meta-analyses of published studies, AF is associated with a 2.4-fold and 1.4-fold increase in the risk of dementia in patients with or without a history of stroke, respectively. This association is independent of shared risk factors such as hypertension and diabetes mellitus. Neuroimaging has illustrated several potential mechanisms of cognitive decline in patients with AF. AF is associated with increased prevalence of silent cerebral infarcts, and more recent data also suggest an increased prevalence of cerebral microbleeds with AF. AF is also associated with a pro-inflammatory state, and the relationship between AF-induced systemic inflammation and dementia remains to be investigated. Preliminary reports indicate that anticoagulation medication including warfarin can reduce the risk of cognitive impairment in patients with AF. Catheter ablation, increasingly used to maintain sinus rhythm in patients with AF, is associated with the formation of new silent cerebral lesions. The majority of these lesions are not detectable after 1 year, and insufficient data are available to evaluate their effect on cognition. Large prospective studies are urgently needed to confirm the association between AF and dementia, to elucidate the associated mechanisms, and to investigate the effect of anticoagulation and rhythm control on cognition. The incidence of atrial fibrillation (AF) and the risk of cognitive impairment both increase with age, and the two pathologies share important risk factors. In this Review, Madhavan and colleagues explore the association and mechanisms of cognitive decline and AF, and discuss potential therapies to prevent cognitive impairment in these patients. Key points Atrial fibrillation is associated with increased risks of dementia and cognitive impairment, independent of history of stroke and other shared risk factors. Proposed mechanisms of cognitive impairment in atrial fibrillation include cerebral thromboembolism, cerebral hypoperfusion, and cerebral microbleeds. Anticoagulation might be protective against cognitive impairment in atrial fibrillation, but further prospective studies are needed. Catheter ablation of atrial fibrillation is associated with new silent cerebral lesions, but the effect on cognitive function is unknown.